A regenerator used in the installation of magnetic refrigeration devices - Botoc, Dorin (JET on-line, 2020)
In this article, the mechanism and functioning of a refrigeration system based on the magnetic system and the magnetocaloric effect are examined. Magnetic refrigeration plants operate based on a state-of-the-art technology that does not contain any toxic refrigerant that is harmful to the environment and the ozone layer. The magnetocaloric effect is created by a rare earth metal called gadolinium. We have studied the benefits of using this type of mechanism for both domestic and industrial needs. High efficiency, net energy consumption lower than the classic, silent systems, and a lack of typical refrigerant characterize this type of installation. The following layout describes the initial prototype for AMR in magnetocaloric refrigeration.
Keywords: alternative technology; alternativne tehnologije; AMR; energetska učinkovitost; energy efficiency; gadolinium material; goldonij; magnetocaloric effect; magnetokalorični učinki